Determinasi Audit Delay pada Perusahaan Manufaktur di Bursa Efek Indonesia - Veronika Sianturi; Adanan Silaban (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to analyze the effect of profitability, company size and solvency on audit delay in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 2019-2021. Data analysis techniques in this study used Descriptive Statistics, Classical Assumption Tests, Multiple Linear Regression Analysis Tests and Hypothesis Tests. Data processing in this study used the SPSS (Statistics Package for the Social Sciences) software version 20. The number of samples obtained from the data collected through observation in the year of the study were 126 samples taken using the purposive sampling method. The results showed that profitability had a negative and significant effect on audit delay, but firm size had a positive and significant effect on audit delay, while solvency had no effect on audit delay.